Multicentre experience with two frozen elephant trunk prostheses in the treatment of acute aortic dissection. (7th March 2019) - Berger, Tim; Weiss, Gabriel; Voetsch, Andreas; Arnold, Zsuzsanna; Kreibich, Maximilian; Rylski, Bartosz; Krombholz-Reindl, Philipp; Winkler, Andreas; Mach, Markus; Geisler, Daniela; Seitelberger, Rainald; Siepe, Mathias; et al.
Abstract: OBJECTIVES: The aim of this study was to evaluate early- and mid-term outcome and aortic remodelling in patients undergoing implantation of 2 different frozen elephant trunk prostheses, either the Thoraflex™ hybrid (Vascutek, Inchinnan, UK) and the E-vita Open (Jotec Inc., Hechingen, Germany) for acute aortic dissection. METHODS: All consecutive patients [ n = 88; median age 59 (49–67) years; 69% male] undergoing surgery with a frozen elephant trunk prosthesis for acute aortic dissection from August 2005 until March 2018 were included in this study. The Thoraflex™ device was implanted in 55 patients and the E-vita Open graft in 33 patients. RESULTS: Preoperative characteristics did not differ significantly between groups. There was also no statistically significant difference in postoperative outcome: in-hospital mortality (11% vs 12%; P > 0.99), stroke (18% vs 6%; P = 0.12) and spinal cord injury (6% vs 6%; P > 0.99). While there was no statistically significant difference in the occurrence of distal stent graft-induced new entries (16% vs 18%; P = 0.77), there was a significantly higher rate of secondary endovascular aortic interventions in the Thoraflex™ hybrid group (22% vs 0%; P = 0.003). There was a trend towards a higher rate of false lumen thrombosis at the level of the stent graft (74% vs 95%; P = 0.085) and was comparable at the thoraco-abdominal transition (53% vs 80%; P = 0.36) 1 year after implantation of the prostheses. CONCLUSIONS: In this comparison of 2 frozen elephant trunk prostheses, there is no evidence that different surgical techniques influence in-hospital outcome. At 1-year follow-up, patients who underwent implantation of the E-vita Open prosthesis showed a significantly reduced rate of secondary aortic interventions and a trend towards a higher rate of false lumen thrombosis which might be attributed to a longer coverage of the descending aorta due to a longer stent graft design and significantly more frequent implantation in zone 3.